The apical leakage of mineral trioxide aggregate as the retrograde filling material with various mjxing agents - , Ema Mulyawati ([Yogyakarta] : Airlangga University Press, 2010)
Background: Mineral trioxide aggregate(MTA) is relatively considered as a new material in endodontic. It even has been used as retrograde filling material due to its biocompability, antibacterial effect, sealing ability and anti-moist effect. Some materials have been used as mixing agents to achieve an appropiate setting of MTA. Purpose: The aim of this study is to investigate the effect of the mixing agents of MTA towards the apical leakage when they are used together as retrograde.filling materials. Methods: The samples of this research consist of 30 human extracted upper central incisors. First, the crown of each tooth is sectioned. The root canals are prepared by using the conventional technique and then are obturated with gutta percha After cutting the root apex, 2 mm from apical, class I cavities are prepared by using fissure bur with the depth of 3mm. The samples then are divided into 3 groups with 10 teeth for each. Group I uses aquabidest as mixing agent of MTA (MTA-aquabidest), groups II uses saline (MTA-saline), while groups III uses 0.12% chlorhexidine (MTA-clilorhexidine). The apex of each group then is filled with the mixing MTA determined already. Afterwards, cIearing methodis used to evaluate the apiculleakage. The apiculleakage actually is determined by meansuring the depth of methylene blue penetration with stereomicroscope. The statictical analyses of the linear dye penetration then are performed with analysis of varian ANOVA. Results: The dye penetration for both MTA-alfuadest and MTA-saline groups indicates the lowest penetration, and there is even a significant difference compared with MTA-0.12% chlorhexidine group( p&lt